Risk factors across the eating disorders - Hilbert, Anja (Psychiatry Res, 2014)
This study sought to examine risk and onset patterns in anorexia nervosa (AN), bulimia nervosa (BN), and binge eating disorder (BED). Women with AN (n=71), BN (n=66), BED (n=160) and non-psychiatric controls (n=323) were compared retrospectively on risk factors, symptom onset, and diagnostic migration. Eating disorder groups reported greater risk exposure than non-psychiatric controls. AN and BED differed on premorbid personality/behavioral problems, childhood obesity, and family overeating. Risk factors for BN were shared with AN and BED. Dieting was the most common onset symptom in AN, whereas binge eating was most common in BN and BED. Migration between AN and BED was rare, but more frequent between AN and BN and between BN and BED. AN and BED have distinct risk factors and onset patterns, while BN shares similar risk factors and onset patterns with both AN and BED. Results should inform future classification schemes and prevention programs.